The universe the vast frontier - Hildebrandt, Jeff; Smith, Dan; Great Pacific Media (Chatswort, CA : AIMS Multimedia, 1997)
Explains the Big Bang theory, the structure and history of the universe, and three major types of galaxies and the difference between them.
Keywords: Universe; Cosmogony -- Juvenile films; Earth -- Origin -- Juvenile films; Big bang theory -- Juvenile films